2002
DOI: 10.1159/000063578
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone Inhibits Rejection of Xenogeneic Transplants in the Sheep Uterus

Abstract: Objectives: One of the proposed roles of progesterone is to prevent maternal immunological destruction of the allogeneic conceptus. Here, it was demonstrated that progesterone allows survival of a xenotransplant placed in the uterine lumen. Methods: Ovariectomized ewes, surgically prepared to have ligatures around each uterine horn, were given daily subcutaneous injections of 50 mg progesterone or vehicle (sesame oil). After 30 days of treatment, mouse hybridoma cells were transplanted to one ligated uterine h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 17 publications
0
26
0
1
Order By: Relevance
“…Among the regulatory processes responsible for inhibition is an immunosuppressive role for progesterone (Majewski and Hansen, 2002;Padua et al, 2005) as well as differentiation of regulatory immune cells that can inhibit inflammation and T cell responses. Among these cells are the M2 macrophage (Gustafsson et al, 2008;Oliveira et al, 2010), γδ T cell (Lee et al, 1992;Suzuki et al, 1995), a n d T r e g c e l l ( A l u v i h a r e e t a l .…”
Section: Immune Response Of the Postpartum Uterusmentioning
confidence: 99%
“…Among the regulatory processes responsible for inhibition is an immunosuppressive role for progesterone (Majewski and Hansen, 2002;Padua et al, 2005) as well as differentiation of regulatory immune cells that can inhibit inflammation and T cell responses. Among these cells are the M2 macrophage (Gustafsson et al, 2008;Oliveira et al, 2010), γδ T cell (Lee et al, 1992;Suzuki et al, 1995), a n d T r e g c e l l ( A l u v i h a r e e t a l .…”
Section: Immune Response Of the Postpartum Uterusmentioning
confidence: 99%
“…During luteal phase or pregnancy, the secretions of the cervical glands become more viscous, forming a plug of thickened mucous in the orifice of the cervix, thus, preventing the coming in of sperm and microorganisms into the uterus [13] . In sheep, one of the progesterone actions is to reduce numbers of specific populations of lymphocytes in the layers of uterine endometrium and hybridoma xenografts [17] . It also played role by hinders rejection or enhances survival of skin allografts placed within the uterine lumen [9] .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in the ovine uterus, low concentrations of progesterone can block tissue graft rejection (Majewski & Hansen 2002, and this has been associated with the induction of a uterine immunoregulatory protein belonging to the serpin family of proteinase inhibitors (see later). The accumulation of macrophages and gd T-cells in the ovine uterus during pregnancy also appears to be partly under sex steroid regulation (Tekin & Hansen 2004).…”
Section: The Endocrine Control Of Intrauterine Inflammatory Activitymentioning
confidence: 99%
“…Studies in sheep and hamsters illustrate that progesterone at concentrations found at the maternal-foetal interface can inhibit tissue graft rejection in utero (Moriyama & Sugawa 1972, Majewski & Hansen 2002. In terms of local effects of progesterone on endometrial/decidual uNK cells, the majority of studies suggest that the immunomodulatory activity may be indirect.…”
Section: Progesterone As An Immunomodulatormentioning
confidence: 99%